2016
DOI: 10.1097/hjh.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in human essential hypertension

Abstract: Abstract:Although the endothelium has a number of important functions, the term endothelial dysfunction is commonly used to describe impairment in its vasodilatory capacity. It is increasingly recognised that this is related to hypertension, although whether it predates hypertension or is a consequence of it is still unknown. In this review we explore the mechanisms of endothelial dysfunction in hypertension, its prognostic significance and methods of pharmacological reversal. Powered by Editorial Manager® an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 133 publications
1
78
0
20
Order By: Relevance
“…Despite intensive clinical and experimental research, the causes of hypertension remain unknown in approximately 95% of all human cases. Endothelial dysfunction (ED) is a common pathology observed in hypertensive humans (Mordi et al, 2016) and rats (Bernatova, 2014). Oxidative stress and nitric oxide (NO) deficiency frequently cause ED in humans and experimental models of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive clinical and experimental research, the causes of hypertension remain unknown in approximately 95% of all human cases. Endothelial dysfunction (ED) is a common pathology observed in hypertensive humans (Mordi et al, 2016) and rats (Bernatova, 2014). Oxidative stress and nitric oxide (NO) deficiency frequently cause ED in humans and experimental models of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several reports have shown that endothelial dysfunction is involved in the genesis or the development of arterial hypertension and may be either the cause or the consequence of the problem. 2,3 In the presence of arterial hypertension there is an imbalance in the production of endothelial factors, thus vasoconstrictors are produced in greater quantity than vasodilators. It explains the impaired endothelium-dependent relaxation in hypertensive animals and human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them were "able to hold the forte, as best as they could, during my short respite and absence". A corollary to this is for the editor to avoid punishment by currying favour and reward from the establishment, in return for diluting the pungency of his editorials, or simply omitting, distorting, and adopting "rhetorical devices" rather than reporting contentious issues in obvious acquiescence to self-censorship (Lee,1998:57 (Mordi, 2008(Mordi, ,2009(Mordi, ,2011(Mordi, ,2012.…”
Section: Voluntary Censorshipmentioning
confidence: 99%
“…Governor Richards' appointment from Jamaica, where he had a record of high handedness in dealing with the educated elite was a clear indication that Britain was not prepared for a peaceful transfer of power soon after the war, thereby igniting Nigeria's militant nationalism. The Zik press constituted the instrument which, along with the NCNC and organized labour sought to merge economic with political grievances (Mordi, 2011), to launch Nigeria on the road to independence. In this regard, the press had derived much inspiration from India, which the Nigerian Daily Times of 11 August 1942 publicized the demands of its nationalists for immediate British withdrawal, and thereby focused world attention on the vast colony and dazzled the imagination of the emergent Nigerian elite .…”
Section: Threat Of Militant Nationalism and Recourse To Enforcement Omentioning
confidence: 99%
See 1 more Smart Citation